Shining light on Drosophila oogenesis: live imaging of egg development - He, Li (Curr Opin Genet Dev, 2011)
Drosophila oogenesis is a powerful model for the study of numerous questions in cell and developmental biology. In addition to its longstanding value as a genetically tractable model of organogenesis, recently it has emerged as an excellent system in which to combine genetics and live imaging. Rapidly improving ex vivo culture conditions, new fluorescent biosensors and photo-manipulation tools, and advances in microscopy have allowed direct observation in real time of processes such as stem cell self-renewal, collective cell migration, and polarized mRNA and protein transport. In addition, entirely new phenomena have been discovered, including revolution of the follicle within the basement membrane and oscillating assembly and disassembly of myosin on a polarized actin network, both of which contribute to elongating this tissue. This review focuses on recent advances in live-cell imaging techniques and the biological insights gleaned from live imaging of egg chamber development.